Implications of Tutors' Continuing Education in The Digital Age - Mantang, Effendi; Juhardi, Juhardi; Tahir, Arifin (IAIN Manado, 2024)
Implications of Tutors' Continuing Education in The Digital Age. This study uses the literature study method to describe the implications of tutors' continuing education in the digital age. The data collection technique is a literature study with relevant research subjects from journals, books, and previous research results. Data analysis of reduction, management, grouping, data interpretation, and conclusion are the focus of research data analysis. Literature study research shows that (1) Education is a place to educate the nation's life, which the 1945 Constitution protects. (2) Non-formal education becomes part of continuing education. (3) Tutor continuing education provides opportunities to improve the quality of knowledge, skills, behavior, and responsibilities of tutorial services in distance education. (4) Digitalization is essential for tutors to refine, understand, and practice online so that tasks and obligations can be carried out correctly and ignore students' interests.